«Healthy Personality» of a Modern University Student as a Research Concept - Zh. V. Puzanova; T. I. Larina (Высшее образование в России)
The issues of physiological and mental health of young people have always remained in the focus of researchers’ attention, however, there are practically no works where the “healthy personality” is considered more broadly, including the features of its functioning in a social context. The authors propose the concept of a “healthy personality”, which includes the following components: emotional stability and psychological well-being, a low degree of suggestibility and adherence to the values of goodness and security. These components meet the challenges of the modern world and underlie the ability of a student’s personality to withstand the challenges of extremism. A combination of techniques was used to create the concept: 1) “General Health Questionnaire” by Goldberg, 2) Schwartz Questionnaire and 3) “Suggestibility Test” by S.V. Klauchek and V.V. Delaryu. With the help of tools that include these methods and thematic blocks (attitudes towards the media, extremism, civic and political position), a questionnaire survey was conducted on a sample of 1,500 people representing the Russian students of three Moscow universities – RUDN University, Moscow State University and National Research University Higher School of Economics in terms of courses and areas of study.The purpose of the article is to develop a research concept of “healthy personality” based on a combination of existing methods used to measure conformity, psychological stability and emotional well-being and value orientations. As a result, the level of emotional stability and psychological wellbeing of Moscow students, the type of value orientations, and their level of conformity are revealed. The dominant personality type, calculated on the basis of the results of the methods, turned out to be “relatively healthy personality” (67.6%), one fifth of the respondents were classified as “healthy personality”, however, every tenth student is a “personality at risk”. The proposed concept can be used during sociological monitoring of educational services of the university in order to diagnose risk groups among first-year students.